Applying ATP bioluminescence to design and evaluate a successful new intensive care unit cleaning programme. Issue 4 (August 2015) - Chan, M.-C.; Lin, T.-Y.; Chiu, Y.-H.; Huang, T.-F.; Chiu, S.-K.; Liu, T.-L.; Hung, P.-S.; Chang, C.-M.; Lin, J.-C.
Summary This was a two-phase prospective intervention study in the cardiology intensive care unit (CICU) and medical intensive care unit (MICU) and of a public 1800-bed medical centre in Taiwan. In phase I, cleaning efficacy was monitored by ATP bioluminescence after daily morning cleaning, and only 43.9% of 221 tested surfaces passed. The baseline data were used to define an intervention consisting of a new cleaning protocol as well as a new education/training programme. In phase II, following the intervention, 88.1% of 270 surfaces were found to be clean. The combined infection rate in the CICU and MICU showed a statistically significant decrease of 49.7%.